Determinants of Carbon Emission Disclosure on Environmental Performance with Green Investment as a Moderating Variable - Hariatih; Rahmah , Ridhan (LifeSciFi, 2025)
Climate change, driven by carbon emissions, has prompted companies to enhance transparency through carbon emission disclosure. However, the relationship between carbon emission disclosure and environmental performance remains debated, particularly due to the lack of an operational mechanism linking the two. This study aims to examine the effect of carbon emission disclosure on environmental performance and to test the moderating effect of green investment. The sample consists of 6 Sharia-compliant companies listed on the Sri-Kehati Index at the Indonesia Stock Exchange from 2020 to 2024, yielding 30 observations. Data were analyzed using a quantitative approach with Partial Least Squares Structural Equation Modeling (PLS-SEM) via SmartPLS version 4. The results indicate that carbon emission disclosure has a positive and significant effect on environmental performance. Furthermore, green investment significantly strengthen this relationship. These findings confirm that carbon emission transparency must be followed by tangible resource allocation to green initiatives to generate substantive environmental impact. The study offers practical implications for regulators and firms in designing effective sustainability strategies grounded in Sharia values.